Topography and dimensions of the auditory tube at the end of the fetal period - O.D. Sapunkov; L.O. Bogdanova; A.L. Kosakovskyi; I.A. Kosakivska; V.V. Syniachenko (Сучасна педіатрія: Україна)
Introduction. Otitis media in premature newborns and term newborns is a serious problem due to the immaturity of the organs and systems of these children and the difficulty of their adaptation. This often leads to the development of pathological changes in the hearing organ and the need for surgical intervention.